СИСТЕМА КОНТРОЛЮ ЗНАНЬ, УМІНЬ УЧНІВ ПРИ ВИВЧЕННІ ДИСЦИПЛІНИ «ЕКОНОМІКА» (Педагогіка вищої та середньої школи, 2022)
In the article the problem of the control of knowledge, abilities, of trainees is considered. Own the variant of the monitoring system of knowledge, abilities of pupils on a subject «Economy» is offered (S. V. Stepanenko s curriculum). The periodic (thematic) control of knowledge, abilities of pupils to the fourth section «National economy» is developed (the program S.V. Stepanenko's «Economy»).